A large-scale social and sports event influence on secondary school pupil's way of life in Almería - María Carrasco Poyatos (FEADEF, 2010)
The aim of the present study was to investigate the influence of a large-scale social and sports event: Mediterranean Games Almería 2005, on secondary school pupil's actual and future way of life. Behavior, demands, motivations, offers and sports practice trends were socially analyzed. This information will allow sports researchers to establish sociodepographic profiles depending on the physical activities demanded. Moreover, official organizations could enhance their plans of action related to sports.